A novel small molecule RAD51 inactivator overcomes imatinib‐resistance in chronic myeloid leukaemia. Issue 3 (22nd January 2013) - Zhu, Jiewen; Zhou, Longen; Wu, Guikai; Konig, Heiko; Lin, Xiaoqin; Li, Guideng; Qiu, Xiao‐Long; Chen, Chi‐Fen; Hu, Chun‐Mei; Goldblatt, Erin; Bhatia, Ravi; Chamberlin, A. Richard; et al.
Abstract RAD51 recombinase activity plays a critical role for cancer cell proliferation and survival, and often contributes to drug‐resistance. Abnormally elevated RAD51 function and hyperactive homologous recombination (HR) rates have been found in a panel of cancers, including breast cancer and chronic myeloid leukaemia (CML). Directly targeting RAD51 and attenuating the deregulated RAD51 activity has therefore been proposed as an alternative and supplementary strategy for cancer treatment. Here we show that a newly identified small molecule, IBR2, disrupts RAD51 multimerization, accelerates proteasome‐mediated RAD51 protein degradation, reduces ionizing radiation‐induced RAD51 foci formation, impairs HR, inhibits cancer cell growth and induces apoptosis. In a murine imatinib‐resistant CML model bearing the T315I Bcr‐abl mutation, IBR2, but not imatinib, significantly prolonged animal survival. Moreover, IBR2 effectively inhibits the proliferation of CD34+ progenitor cells from CML patients resistant to known BCR‐ABL inhibitors. Therefore, small molecule inhibitors of RAD51 may suggest a novel class of broad‐spectrum therapeutics for difficult‐to‐treat cancers.